Haemoglobin H disease in 2 Filipino families. Issue 4 (August 1978) - Horne, M K; Walters, C; Reeves, J D
Abstract : Haemoglobin H disease is described in successive generations of 2 Filipino families. The condition was asymptomatic. The inheritance pattern of haemoglobin H disease in these families appeared to be like that described for Thais.